A New Bathymetry for the Southeastern Filchner‐Ronne Ice Shelf: Implications for Modern Oceanographic Processes and Glacial History. Issue 7 (5th July 2018) - Rosier, S. H. R.; Hofstede, C.; Brisbourne, A. M.; Hattermann, T.; Nicholls, K. W.; Davis, P. E. D.; Anker, P. G. D.; Hillenbrand, C.‐D.; Smith, A. M.; Corr, H. F. J.
Abstract: The Filchner‐Ronne Ice Shelf, the ocean cavity beneath it, and the Weddell Sea that bounds it, form an important part of the global climate system by modulating ice discharge from the Antarctic Ice Sheet and producing cold dense water masses that feed the global thermohaline circulation. A prerequisite for modeling the ice sheet and oceanographic processes within the cavity is an accurate knowledge of the sub‐ice sheet bedrock elevation, but beneath the ice shelf where airborne radar cannot penetrate, bathymetric data are sparse. This paper presents new seismic point measurements of cavity geometry from a particularly poorly sampled region south of Berkner Island that connects the Filchner and Ronne ice shelves. An updated bathymetric grid formed by combining the new data with existing data sets reveals several new features. In particular, a sill running between Berkner Island and the mainland could alter ocean circulation within the cavity and change our understanding of paleo‐ice stream flow in the region. Also revealed are deep troughs near the grounding lines of Foundation and Support Force ice streams, which provide access for seawater with melting potential. Running an ocean tidal model with the new bathymetry reveals large differences in tidal current velocities, both within the new gridded region and further afield, potentially affecting sub‐ice shelf melt rates. Plain Language Summary: The Filchner‐Ronne Ice Shelf in Antarctica is the largest body of floating ice in the world and plays an important role in the global climate system through its interactions with the ocean and Antarctic Ice Sheet. Due to its thickness and remoteness, the shape of the large ocean cavity beneath this floating ice shelf is poorly understood, yet this information is crucial for ice and ocean models of the region. In this study we present recent measurements of the thickness of this ocean cavity and, in combination with previous measurements, produce a new map of the area. A number of new features are revealed in this map, and we discuss the implications for ocean currents within the cavity, as well as past and future ice sheet flow. Key Points: Data from a recent seismic survey of the southeastern Filchner‐Ronne Ice Shelf are presented Together with previous measurements, a new bathymetric grid of the region is produced New features identified in the grid have important oceanographic and glaciological implications